Analisis Hukum Nafkah Anak Hasil Sewa Rahim Menurut Ulama Mazhab - Bunga Annisa; Ahmad Syafi'i SJ; Diyan Putri Ayu (Social Science Academic, 2023)
In medicine, technological development is an advantage to create a novel way that makes easier for couples to have children, its surrogate mother. That is conception outside the womb and baby’s seed planted in the womb of another woman who has been hired so the wife will not pregnant. Surrogate mother is a matter of debate for clerics because nasab mixed between a married couple and a surrogate mother that will sever the child’s nasab with the father. In addition, nasab’s decision resulted in a loss of the obligation of the father to provide his child’s rights as well as the living rights. The study was researched with two formula problems: 1) what was the status of the child of surrogate mother according to clerics of mazhab?, 2) how does the law of child’s living rights of surrogate mother according to cleircs of mazhab?. The study uses library research study methods through data sources of books, journals, and literature. Based on research, it can be summed up: 1) the status of the child of surrogate mother in Ali Akbar and Husein Yusuf’s view is viewed as an illegitimate child and is condemned as a adultery child in Islam; 2) the law of child’ living of surrogate mother according to mazhab Hanafi and Syafi’i was deemed unobligatory to the father because of failure of nasab, but in the maslahah mursalah theories if illegitimate child’s living was compulsory for the child’s welfare to adulthood.